1998
DOI: 10.1152/jn.1998.80.3.1427
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Effect for Neural Spike Time Reliability

Abstract: The spike timing reliability of Aplysia motoneurons stimulated by repeated presentation of periodic or aperiodic input currents is investigated. Two properties of the input are varied, the frequency content and the relative amplitude of the fluctuations to the mean (expressed as the coefficient of variation: CV). It is shown that, for small relative amplitude fluctuations (CV approximately 0.05-0.15), the reliability of spike timing is enhanced if the input contains a resonant frequency equal to the firing rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 57 publications
(4 reference statements)
6
121
0
Order By: Relevance
“…3g). Across the two trials the neuron will thus produce distinct spike patterns 18,26 , as observed in vitro 19,23 . When there is a prolonged period without spiking on both trials, the voltage trajectories will converge back and the same spike pattern will be obtained.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…3g). Across the two trials the neuron will thus produce distinct spike patterns 18,26 , as observed in vitro 19,23 . When there is a prolonged period without spiking on both trials, the voltage trajectories will converge back and the same spike pattern will be obtained.…”
mentioning
confidence: 89%
“…Simple models of an in vitro preparation in which synaptic transmission is blocked and the same somatic current is injected repeatedly suggest that imprecision is mainly due to variability in the membrane voltage just before the spike, and that this is inversely proportional to the rate of change of the voltage 19,20 . Thus, a precisely timed spike follows a rapidly depolarizing current.…”
Section: Factors Affecting Reliability and Precisionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been done in a variety of neuronal cell classes (Brumberg 2002, Carrandini et al 1996Hutcheon et al 1996;Nowak et al 1997;Hunter et al 1998;Volgushev et al 1998;Fellous et al 2001). Results suggest that cortical pyramidal neurons can be viewed as non-linear oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that cortical pyramidal neurons can be viewed as non-linear oscillators. Additionally, subthreshold resonances intrinsic to the membrane have significant impact on the response properties of cortical neurons (Llinas 1991;Hutcheon et al 1996;Hunter et al 1998). This in turn could imply a certain degree of nonlinearity in the firing patterns of neurons in response to stimuli of varying frequencies.…”
Section: Introductionmentioning
confidence: 99%